Screening and identification of genes associated with flight muscle histolysis of the house cricket Acheta domesticus - Lu, Ying; Wang, Zizhuo; Lin, Fei; Ma, Yuqing; Kang, Jiangyan; Fu, Yuying; Huang, Minjia; Zhao, Zhuo; Zhang, Junjie; Chen, Qi; Ren, Bingzhong (Frontiers in Physiology, 2023)
Flight muscle histolysis, as an important survival strategy, is a widespread phenomenon and contributes to the adaptation to the external environment of various insect taxa. However, the regulatory mechanism underlying this phenomenon in Orthoptera remains unknown. The house cricket Acheta domesticus is a suitable model for studying flight muscle histolysis due to its biology. In this study, the key genes associated with flight muscle histolysis in A. domesticus were investigated by transcriptomics and RNA interference. The results showed that flight muscle histolysis in A. domesticus was standard and peaked within 9 days after eclosion of adult crickets, and there were no significant differences in the peak time and morphology of flight muscle histolysis between males and females. In addition, the differentially expressed genes between before and after flight muscle histolysis were studied, of which fatty-acid binding protein (FABP), troponin T and actin were identified as candidate genes, and after injecting the dsRNA of these three candidate genes, only the downregulated expression of FABP led to flight muscle histolysis of A. domesticus. These findings lay a molecular foundation of flight muscle histolysis for exploring the trade-off between dispersal and reproduction in Orthoptera and other insects with this phenomenon.